Paradigma Masyarakat Terhadap Gerakan Politik Fundamentalisme Hindu di Bali - Indra Harahap; Sintia Maunasah Bako (Tarbiatuna: Journal of Islamic Education Studies, 2023)
Hindu fundamentalism is the thinking of a group of people who tend to prove religious and political reform in Hinduism. The emergence of fundamentalism is due to cultural, social, political and ideological problems. Where ideology is the goal of fundamentalism to regulate the political system of economic resources and others.The method used in this research is qualitative method. The purpose of this study is to discuss how the views / ways of thinking of the community are related to the Hindu fundamentalist political movement. The results of this study indicate that Hinduism has high religious fundamentalism and political tolerance Keywords: paradigm, politics, Hindu fundamentalism